Jump-Stay Rendezvous Algorithm for Cognitive Radio Networks - Liu, Hai; Lin, Zhiyong; Chu, Xiaowen; Leung, Yiu-Wing (IEEE transactions on parallel and distributed systems, 2012)
Cognitive radio networks (CRNs) have emerged as advanced and promising paradigm to exploit the existing wireless spectrum opportunistically. It is crucial for users in CRNs to search for neighbors via rendezvous process and thereby establish the communication links to exchange the information necessary for spectrum management and channel contention, etc. This paper focuses on the design of algorithms for blind rendezvous, i.e., rendezvous without using any centralized controller and common control channel (CCC). We propose a jump-stay channel-hopping (CH) algorithm for blind rendezvous. The basic idea is to generate CH sequence in rounds and each round consists of a jump-pattern and a stay-pattern. Users "jump" on available channels in the jump-pattern while "stay" on a specific channel in the stay-pattern. We prove that two users can achieve rendezvous in one of four possible pattern combinations: jump-stay, stay-jump, jump-jump, and stay-stay. Compared with the existing CH algorithms, our algorithm has the overall best performance in various scenarios and is applicable to rendezvous of multiuser and multihop scenarios. We derive upper bounds on the maximum time-to-rendezvous (TTR) and the expected TTR of our algorithm for both 2-user and multiuser scenarios (shown in Table 1). Extensive simulations are conducted to evaluate the performance of our algorithm.